Pengembangan Sumber Daya Guru Melalui Program Pengabdian Pre dan Pasca SMA Bina Insan Mandiri (BIMA) di Pondok Pesantren al-Ihsan Baron - Sureni Sureni (Pascasarjana IAIN Metro, 2022)
This research was conducted to obtain information by analyzing the development of teacher resources carried out at the Al-Ihsan Baron Islamic Boarding School. Given the importance of the need for human resources in Islamic educational institutions, especially the needs of ideal teachers by the vision and mission criteria of the Al-Ihsan Baron Islamic Boarding School as well as the fulfillment of competent and professional teacher resources. Thus, a service program aimed at graduates or Post High School Bina Insan Mandiri (BIMA) was born. Types of teacher resource development programs include (1) Parenting Assistant (2) Short-Term Teacher Service and (3) Long-Term Teacher Service. Through this development program, it is hoped that it can meet the needs of qualified educators so that they can optimize skills and performance to create quality institutions and education. This research is descriptive research with a qualitative approach. Data collection techniques using observation techniques, interviews, and documentation. The results of the study suggest that the potential of teacher resources coming from graduates/outputs from institutions can contribute and contribute to educational institutions internally, namely through service programs, which can carry out their duties and utilize knowledge to students according to their expertise and abilities.